Toward early diagnosis of oral cancer: Diagnostic utility of cytomorphological features, a pilot study - Jairajpuri, Zeeba Shamim (Natl J Maxillofac Surg, 2019)
INTRODUCTION: Early detection of oral cancer is one of the most efficient ways to reduce the high mortality from this disease because of the ready accessibility of the oral cavity. We need to devise urgent diagnostic tools to detect early oral premalignant and malignant lesions. AIM: The aim of the present study was to grade the oral lesions in an attempt toward developing a novel cytological grading system. Further, morphometric analysis of cellular parameters was also performed to compare their significance in differentiating benign from malignant lesions. MATERIALS AND METHODS: The present study was conducted at a tertiary care hospital catering to the low socioeconomic population. Patients presenting in the various Out Patient Departments with suspicious oral lesions were evaluated by cytology in the Department of Pathology. RESULTS: A total of 72 patients were evaluated with a mean age of 43.54 ± 10.35 years. The involvement of the buccal mucosa was the most common site of oral lesions. Cytologically, the lesions were graded according to the oral/oro-pharyngeal cytology grading system into grades A to F. Cyto-morphometric analysis showed an increasing trend in mean nuclear diameter from benign to malignant cases while the mean cytoplasmic diameter decreased, value of P < 0.05 was observed indicating a statistically significant difference between the two groups. CONCLUSIONS: Cytological features of pleomorphism are a unique feature in oral carcinoma reflecting intracellular alterations in cells. Grading of lesions according to cytological characteristics can be helpful in standardizing the reporting of the oral lesion. However, our study was restricted by limited data; we emphasize more extensive studies to assess the usefulness and applicability of such a grading system. We also conclude that the use of cytomorphometry can improve the diagnostic reliability of exfoliative cytology.